DOMINASI CYANOBACTERIA PADA MUSIM PERALIHAN DI PERAIRAN LAUT BANDA DAN SEKITARNYA (Makara Journal of Science, 2004)
Domination of Cyanobacteria at Transition Monsoon around Banda Sea Area. Banda Sea had affected by monsoon factor, this condition also influenced fitoplankton condition, but information about fitoplankton condition especially Cyanobacteria group still not complete yet. Therefore had done the researched about fitoplankton in October 1998 and November 1999, that months is regarded as vice of transition monsoon. Fitoplankton samples were taken from the surface to 200 m depth to known the abundant, composition, and distribution of Cyanobacteria. The results showed that the abundant of Trichodesmium erahtraeum varied between 0.02-1.2 x 102 coloni m-3, the highest vale found in 100 m depth and the lowest in 200 m depth. The abundance of Trichodesmium thiebautii varied between 0-8.8 x 102 cel m-3. Distribution of Trichodesmium erythraeum found until 50 m depth, their abundance high relative, this condition caused by nitrate concentration (r2 =28,30 %) and temperature (r2 =17,30 %). Based on their abundance, diversity, evenness and distribution Trichodesmium eryhtraeum dan Trichodesmium thiebautii dominated in transition monsoon.